1991
DOI: 10.1090/s0002-9939-1991-1049841-5
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between density and weak density in Boolean algebras

Abstract: Abstract.Given a homogeneous, complete Boolean algebra B, it is shown that d(B) < min(2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This function was introduced in Bozeman [2] where it is shown that hwd(A) is the minimum size of a set, X, such that for all a A + the set {a · x: x X} cannot be 2-reaped in A E a. Note in Bozeman [2] the terminology weakly dense is used instead of ''cannot be 2-reaped''. Also note that if a set is dense in A then this set is also hwd in A and so hwd(A) 5 y(A).…”
Section: Homogeneous Weak Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…This function was introduced in Bozeman [2] where it is shown that hwd(A) is the minimum size of a set, X, such that for all a A + the set {a · x: x X} cannot be 2-reaped in A E a. Note in Bozeman [2] the terminology weakly dense is used instead of ''cannot be 2-reaped''. Also note that if a set is dense in A then this set is also hwd in A and so hwd(A) 5 y(A).…”
Section: Homogeneous Weak Densitymentioning
confidence: 99%
“…By lemma 6.3 we have hwd(A) ] c(A) for complete BA's. In Bozeman [2] it is shown that if A is complete and homogeneous for the functions y and hwd then r 2 (A)= hwd(A). He also shows, assuming GCH, that if A is complete and homogeneous in y and hwd then y(A) = hwd(A).…”
Section: Lemma 64 Suppose a Is An Infinite Ba And X ¤ A Such That Xmentioning
confidence: 99%
“…This function has been extensively studied in the general context of Boolean algebras. See, for example, Balcar and Simon [1992], Peterson [1998], Bozeman [1991], Monk [1996].…”
mentioning
confidence: 99%